Interplay of wall force field and wall physical characteristics on interfacial phenomena of a nano-confined gas medium - Rabani, Reza; Heidarinejad, Ghassem; Harting, Jens; Shirani, Ebrahim (International Journal of Thermal Sciences, 2020)
The effect of the wall force field and the wall physical characteristics on the interfacial phenomena of a 5.4 nm nanoconfined gas medium are investigated by applying three-dimensional molecular dynamics simulations. Assuming that a range of 1 nm from each wall is affected by the wall force field, the gas distribution changes notably in this region which covers 40% of the channel height. Therefore, a combined effect of the wall force field and the wall stiffness, its mass as well as the interaction strength determines the interfacial phenomena such as interfacial thermal resistance (ITR) at the gas/solid interface. The increment in interaction strength of the gas/solid atoms leads to an increase in the amount of adsorbed gas on the wall which reduces the temperature jump and ITR notably. When the ratio between the interaction strengths of the gas/solid to the gas/gas atoms exceeds 4, the temperature jump and the ITR reduce to zero. As the wall becomes stiffer, the temperature jump and consequently the ITR are increased considerably. Simultaneously, the temperature distribution in the gas medium along the channel height becomes more and more independent of the gas density as the wall stiffness increases. It is observed that as the ratio between the mass of the wall and the gas atoms increases up to 2, the temperature jump reduces notably. Meanwhile, as the wall atoms become heavier, an increment in the temperature jump is observed. Consequently, the minimum ITR occurs at a ratio of 2. It is also shown that the temperature profile in the bulk region of the channel is approximately independent of the wall mass. Considering several metals as the wall material, our analysis reveals that silver, copper, and nickel experience the least ITR among the others.
CRIS-Team Scopus Importer:2020-04-07
Keywords: Dense gas; Dilute gas; Gas adsorption; Interfacial thermal resistance; Temperature jump